The Effect of Liquidity and Solvability Ratio of Liquidity - Ria Rosalia Simangunsong (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to determine the Effect of Liquidity and Solvency Ratios on Profitability at PT. Surya Baru in Jakarta. The method used is explanatory research with a sample of 8 years of financial statements. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Current Ratio significant effect on Return on Assets of 46.5%, hypothesis testing obtained significance of 0.042 <0.05. Debt to Asset Ratio has a significant effect on Return on Assets by 76.9%, the hypothesis test obtained significance of 0.004 <0.05. Current Ratio and Debt to Asset Ratio simultaneously have a significant effect on Return on Assets of 82.4%, the hypothesis test obtained significance of 0.013 <0.05.